Lamellar porous vermiculite membranes for boosting nanofluidic osmotic energy conversion. Issue 25 (18th June 2021) - Cao, Li; Wu, Hong; Fan, Chunyang; Zhang, Zhiming; Shi, Benbing; Yang, Pengfei; Qiu, Ming; Khan, Niaz Ali; Jiang, Zhongyi
Abstract : We demonstrate an efficient nanofluidic osmotic energy generator based on lamellar porous vermiculite membranes (PVMs) which offer high transmembrane ion flux and ion selectivity, showing superior power density. Abstract : Lamellar membranes with two-dimensional nanofluidic channels hold great promise in harvesting osmotic energy from salinity gradients. However, the power density is often limited by the high transmembrane resistance primarily caused by the tortuous interlayer ion diffusion pathway. Here, we demonstrate the great potential of lamellar porous vermiculite membranes (PVMs) as efficient nanofluidic osmotic energy generators. The artificial in-plane nanopores on vermiculite nanosheets dramatically decrease the tortuosity and offer additional vertical ion pathways, substantially elevating the transmembrane ion flux. Meanwhile, the confined interlayer spacing serves as the selective barrier, contributing to a high ion selectivity. When operating under a 1000-fold salinity gradient, the PVMs achieve a 16-fold increase in output power density compared with nonporous vermiculite membranes, with a maximum value of 10.9 W m −2 that outperforms those of most of the state-of-the-art 2D lamellar membranes.